A suite of ground motion prediction equations for cumulative absolute velocity in shallow crustal earthquakes including epistemic uncertainty. Issue 2 (May 2021) - Bullock, Zach; Liel, Abbie B; Dashti, Shideh; Porter, Keith A.
Recent research has highlighted the usefulness of cumulative absolute velocity( CAV ) in several contexts, including using theCAV at the ground surface for earthquake early warning and using theCAV at rock reference conditions for evaluation of the liquefaction risk facing structures. However, there are relatively few ground motion prediction equations for CAV, they are based on relatively small data sets, and they give relatively similar results. This study develops nine ground motion prediction equations forCAV based on a global database of ground motion records from shallow crustal earthquakes. Its provision of nine models enables characterization of epistemic uncertainty for ranges of earthquake characteristics that are sparsely populated in the regression database. The functional forms provide different perspectives on extrapolation to important ranges of earthquake characteristics, particularly large magnitude events and short distances. The variability and epistemic uncertainty in the models are characterized. Spatial autocorrelation of the models' errors is investigated. The models' predictions agree with existing broadly applicable models at small to moderate magnitudes and moderate to long distances. These models can be used to improve hazard analysis ofCAV that incorporates the influence of epistemic uncertainty.